Analysis of fishing vessel capsizing causes and links to operator stability training. (October 2019) - Davis, Bryan; Colbourne, Bruce; Molyneux, David
Highlights: The primary cause of most incidents can be attributed to operators' decisions that are detrimental to stability. Near misses were used to supplement this data. Near misses, however, proved difficult to collect. Discussions with operators highlighted the impact training has on an individual's understanding of stability and the decisions they make while fishing. Reduction in capsizing events in Canada may be attributed to training requirements become more strict. Confident that improved training among operators will lead to a significant reduction in capsizing events in the future. Abstract: Commercial fishing is one of the most dangerous industries in the world. Although fishing vessel capsizes are rarely occurring events, they result in a disproportionally high fatality rate. In Canada, such fatalities are a significant problem. This study's objectives are to determine the primary causes of fishing vessel capsizing and recommend measures to reduce the frequency of fishing vessel capsizes. A significant part of the data collection for the study is focused on the fishing industry in Newfoundland and Labrador, Canada, although the conclusions are more widely applicable. Through an analysis of national and international fishing vessel capsizing accident investigation reports, the study identifies the primary causes of capsizing events. In 57 of the 60 capsizes analyzed, operators' actions played a significant role. Through interviews and discussions with fishing vessel operators, this data was supplemented and reinforced with a preliminary investigation of capsizing near-misses. The concept of near-miss reporting has been successfully used in other industries to identify hazards and improve safety culture. The study also focused on operator and crew understanding of vessel stability. This revealed a correlation between the amount of formal training an operator had received and their understanding of stability. Those who had received stability training were better equipped to avoid or manage potential capsizing events. Many fishing vessel capsize events were attributed to operator error and operators with no stability training are more likely to make poor decisions based on lack of knowledge or common misconceptions of vessel stability. A compulsory stability education course for the fishing industry is recommended along with a trial program of formalized near-miss reporting.